Integration among Psychology, Technology, and Culture: A Systematic Literature Review - Harjo Seputro; Abdul Halik; Dheny Jatmiko; Eko April Ariyanto (SEMINAR NASIONAL KONSORSIUM UNTAG SE INDONESIA, 2024)
This study aims to examine the integration of psychology, technology, and culture through a systematic literature review. With the rapid advancement of digital technology, the interaction between individuals, society, and technology has deepened, influencing various psychological and cultural aspects. This review explores various theories and models that underpin the understanding of the impact of technology on human behavior, psychological development, and the influence of culture in the use and acceptance of technology. Additionally, the study identifies challenges in understanding the role of culture in shaping psychological responses to technology, as well as how these factors interact in an increasingly interconnected global context. Key findings highlight the complex relationship between the three aspects, where technology not only affects individuals psychologically but also shapes evolving cultural values and norms. The study suggests further research to better understand the dynamics between psychology, technology, and culture, and their